Reorganization of the Assembly Station in the Production Process of the Sliding Floor for Reloading Ramps in the Context of Improving the Quality of the Finished Product - Magdalena Dąbrowska; Daniel Medyński; Wiktor Bieliński; Krzysztof Kolbusz (Technologia i Automatyzacja Montażu)
The paper presents the definitions of the term quality quoted in the literature on the subject. FMEA (Failure Mode and Effects Analysis) methodology was presented. A reloading ramp was characterized as the subject of the study. A cause-and-effect analysis of non-compliance in the finished product was performed using the Pareto-Lorenz diagram, Ishikawa diagram and brainstorming. The FMEA analysis of the assembly table indicated the elements of the workstation causing the most frequently occurring non-conformities. Based on the obtained results, corrective actions were proposed to reorganize the assembly station. The implemented activities made it possible to reduce the critical RPN coefficients for the elements of the assembly table and to shorten the time necessary to make one piece of the finished product.